EFEKTIVITAS TINDAKAN AMBULASI DINI TERHADAP PENURUNAN NYERI PUNGGUNG POST KATETERISASI JANTUNG KLIEN DENGAN SINDROM KORONER AKUT (SKA): SEBUAH STUDI KASUS DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Rahmanisa, Tengku Atika; Rasyid, T. Abdur (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Acute coronary syndrome (ACS) is a disease in which blood flow to the heart is decreased. Cardiac catheterization is one of the medical interventions to treat ACS. Post-catheterization patients must be immobilized to prevent hematoma and bleeding in the insertion area. Back pain was one of the complaints frequently reported by patients who were required for strict bed rest and immobilization after cardiac catheterization. The purpose of this study with the application of nursing care to Mr. Y and Mr. D with the implementation of early ambulation to reduce the discomfort of post-cardiac catheterization back pain in the CVCU room of Arifin Achmad Hospital, Riau Province strarted from 10th June – 17th June 2023. The analyze nursing care for patients' back pain with early ambulation after cardiac catheterization on implementation of early ambulation begins with a head bed 15o, head bed 30o, lateral position opposite to the puncture site as one piece, and then Patients were also advised to walk around the room and use the bathroom if they wanted. Based on the results of the early ambulation, it was found that the pain scale before Mr. Y was VAS 5 (moderate pain) and Mr. D VAS 4 (moderate pain). After early ambulation, the back-pain scale of Mr. Y was VAS 1 (mild pain), and Mr. D's pain scale was VAS 3 (mild pain). The above study concludes that the application of early ambulations can increase the patients' back pain.